EXPLORING THE DRIVERS OF PURCHASING DECISIONS IN LAZADA - Fariez Tachsin; Nurul Aisyah Rachmawati (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
E-commerce, or electronic commerce, has become a major pillar of the modern economy by changing the way we buy, sell and interact in the global marketplace. This study aims to determine the influence of perceived ease, perceived benefits, and perceived risk on purchasing decisions with purchasing interest as a mediating variable. The number of samples in this study was 100 respondents. Data collection techniques using questionnaires. Data analysis methods using SEM PLS. The results of the study indicate that Perceived Ease of Use, Perceived Benefits and Perceived Risk have a significant effect on Purchase Intention and Purchase Decision. Purchase Intention has a significant effect on Purchase Decision. Purchase Intention has not been able to mediate the effect of Perceived Ease of Use and Perceived Risk on Purchase Decision. However, Purchase Intention is able to mediate the effect of Perceived Benefits on Purchase Decision.